A SUSTENTABILIDADE DAS ORGANIZAÇÕES As estratégias discursivas do Guia Exame - BACCO, EDI LUIZA (2015)
The sustainability culture has increasingly standing out in organizations, whether with relevant projects or just as constructed speeches in order to add value to their image. The specialized media is responsible for disclosing these companies’ actions. The goal of this study is investigate the sustainability ethos constitution on Guia Exame, from Editora Abril, mainly in the evidences that can indicate pedagogical, doctrinal and authoritarian speeches. The question that frameworks this research is: Which kind of sustainable company model the publication suggests/impose? It seeks to evaluate if the sustainability notion was reassigned on Guia Exame since its launch in 2000. We mobilized theoretical and methodological devices from Discursive Analysis (PÊCHEUX and ORLANDI), focused on the ethos identification and scenography (MAINGUENEAU). Starting from a protocol, it was adopted and pattern to analyze the corpus: covers and reading letters of 15 editions. The publication analyses revealed the conductor ethos, the one that guides the reader, as a didactic and authoritarian teacher. It was also verified, that in the meanings circulation, these 15 years of the guide, an updated on the sustainability concept. This redefinition embodies meanings in historical and social context, making the sustainability notion increasingly more extensive.